INVENTARISASI BAHAN TAMBANG DI WILAYAH CIBADAK, CIEMAS DAN CISAAT, KABUPATEN SUKABUMI - -, M. Sapari D. Hadian; -, Cipta Edyana (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
Nowaday natural resources have to be optimalized for humanitarian welfare, It needed manajemen of mining effort that have the same with characterization of each natural resourses, then it needed to take inventory of appearance of natural resources itself. All the information of mineral deposits be fitured in Map that covered in Identification and Mapping Potential Mineral Resourses Work.South Mountained Zone is a Table Land which developed a triangle with its top at southern Bandung have direction west to east, from The Pelabuhan Ratu Bay until Nusakambangan. Width of South Mountained Zone is about 50km. This zone is divided into 3 subzones, which is Jampang Subzone, Pangalengan Subzone, and Karangnunggal Subzone. The research area is included in Jampang subzone that contain Pra-tertiary Rock and Tertiary Sediment and appears in western of this zone. The Oldest rock found at South Mountained Block West Java consist igneous rock, ultrabase, and basalt (Van Bemmelen, 1949) and Skish which appears in Pra-tertiary age (Mark, 1957). Endang Toyib (1975) comment that complex melange deposits which is consist in Ciletuh area are the oldest rock (Mps, Mgg, Mgp). Those rocks formed by ofiolith and metamorphic rock and sedimentary rock consist black clay that scraped and mixed tectonically.